Investigation of Production and Price Relationship in Cow Milk Production by Koyck Model Approach - Damla Özsayın (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to investigate the relationship between the amount of cow milk production and its price in Turkey in the period between 1985-2015.The Koyck model that is one of the distributed lag models was used to analyse of these data. The production of cow milk was considered as dependent variable and the price series consisting of cow milk prices and lagged price series are considered as explanatory variable in the model. According to the results of Koyck model, it was determined that the production of cow milk was affected by the prices of maximum one year retrospectively and the time required to dramatically affect to production of cow milk of the change taken place in prices of cow milk was 2.9 years. Furthermore, the increase of 1 TL in price of cow milk decreases the production of cow milk by 183372.4 tonnes. On the other hand, the increase of 1 TL in prices in the previous period decreases the production of cow milk by 137345.9 tonnes. Based on these data, it can be said that the price of cow milk composed in the free market conditions is rather efficient in determination to production amount. In conclusion, economic measures such as making of production planning, constituting of efficient marketing opportunities, price policies and giving a place to stable production can be taken against to fluctutations in the price increases.